The Psychometric Properties of the Norwegian version of Adolescent Sleep-Wake Scale (ASWS) - Hysing, Mari; Jakobsen, Reidar (PsykTestBarn, 2017)
Description: The Adolescent Sleep-Wake Scale (ASWS) is a 28-item self-report questionnaire that assesses sleep and sleep behaviors in 12- to 18-year-old adolescents. The adolescents are asked to indicate how often sleep behaviors have occurred during the past month using a 6-point scale (never to always). In addition to the total scale score, five subscale scores can be calculated. The ASWS takes 10 to 15 minutes to complete. The original version was developed by LeBourgeois and colleagues. The instrument was translated to Norwegian by professor Ståle Pallesen, University of Bergen and SOVno. Literature search: The literature search did not identify any Norwegian studies that met the inclusion criteria. Psychometrics: The psychometric properties of the ASWS have not been documented in Norwegian or Nordic studies so far. Conclusion: Since no information regarding the psychometric properties of the Norwegian version of ASWS is available, it should be used with great caution. Norwegian population based studies that examine the psychometric properties of ASWS are needed.